2012
DOI: 10.1673/031.012.0101
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Source and Diet affect Development and Reproduction ofOrius thripoborusandOrius naivashae, two Predatory Anthocorids from Southern Africa

Abstract: The effect of moisture source and diet on the development and reproduction of the pirate bugs, Orius thripoborus (Hesse) and Orius naivashae (Poppius) (Hemiptera: Anthocoridae) was examined in the laboratory. Both species had been collected in and around sugarcane fields in South Africa. Supplementing eggs of the flour moth Ephestia kuehniella (Zeller) (Lepidoptera: Pyralidae) with a green bean pod as a moisture source yielded better nymphal survival and faster development, as compared with free water encapsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…Although for O. thripoborus sex ratios at all temperatures were essentially 1:1, skewed sex ratios in O. naivashae observed by Bonte et al (2012) were conÞrmed in the current study. In the latter species, sex ratios were female biased, except at 23ЊC.…”
Section: Development Developmental Parameters Ofsupporting
confidence: 61%
See 2 more Smart Citations
“…Although for O. thripoborus sex ratios at all temperatures were essentially 1:1, skewed sex ratios in O. naivashae observed by Bonte et al (2012) were conÞrmed in the current study. In the latter species, sex ratios were female biased, except at 23ЊC.…”
Section: Development Developmental Parameters Ofsupporting
confidence: 61%
“…So far, it is not clear which mechanisms are involved in the female biased sex ratios observed in our O. naivashae population. Bonte et al (2012) reported a better lifetime oviposition of O. thripoborus at 23ЊC compared with that of O. naivashae. In the current study, fecundities and egg hatch rates were superior at 25ЊC for both species, and again, O. thripoborus produced more eggs than O. naivashae.…”
Section: Development Developmental Parameters Ofmentioning
confidence: 95%
See 1 more Smart Citation
“…This may be due to the different nutritional requirements of the immature versus adult stages of O. thripoborus , or to differences in their capacity to handle the astigmatid prey. Previous studies (Bonte et al ., , 2015) demonstrated a higher level of nutritional plasticity in O. thripoborus as compared with O. naivashae . This difference was confirmed on all tested foods in the present study, and was more pronounced on a less optimal prey, like the astigmatid mites.…”
Section: Discussionmentioning
confidence: 96%
“…(Bonte and De Clercq , ; Bonte et al. ). The plants and artificial oviposition substrates were examined for eggs daily to determine the pre‐oviposition period.…”
Section: Methodsmentioning
confidence: 99%